1998
DOI: 10.1172/jci2592
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of monocyte-endothelial cell interactions by platelet microparticles.

Abstract: Platelets, activated by various agonists, produce microparticles (MP) from the plasma membrane, which are released into the extracellular space. Although the mechanism of MP formation has been clarified, their biological importance remains ill defined. We have recently shown that plateletderived MP influence platelet and endothelial cell function. In this study, we have further examined the mechanism of cellular activation by platelet MP. To address the possibility that they may influence monocyte-endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
395
0
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 507 publications
(406 citation statements)
references
References 54 publications
4
395
0
7
Order By: Relevance
“…Arachidonic acid is a major mediator of the cellular effects of microparticles (32,(37)(38)(39). We previously demonstrated that microparticles shuttle arachidonic acid from leukocytes to fibroblasts (30).…”
Section: Discussionmentioning
confidence: 99%
“…Arachidonic acid is a major mediator of the cellular effects of microparticles (32,(37)(38)(39). We previously demonstrated that microparticles shuttle arachidonic acid from leukocytes to fibroblasts (30).…”
Section: Discussionmentioning
confidence: 99%
“…P-selectin, which is present on platelet-derived microparticles, triggers monocytes to express not only tissue factor, but also chemokines (41,42). Platelet-derived microparticles transport arachidonic acid to endothelial cells and induce the expression of cyclooxygenase 2 and the increased production of prostacyclin (43), enhance the interaction between monocytes and endothelial cells (44), and enhance leukocyte aggregation and their accumulation on the endothelium (45). Furthermore, thrombin, factor Xa, and fibrin degradation products are all potent inducers of the inflammatory response (46)(47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to activated platelets, PMP can express 50-100 fold higher procoagulant activity (Sinauridze, Kireev, Popenko, Pichugin, Panteleev, Krymskaya, and Ataullakhanov 2007). They retain selected platelet membrane constituents, including glycoproteins Ib, IIbIIIa, and P-selectin (Gawaz, Ott, Reininger, Heinzmann, Neumann 1996;George, Pickett, Saucerman, McEver, Kunicki, Kieffer, and Newman 1986) which support vascular inflammation by participating in heterotypic communication with leukocytes and vascular endothelial cells (Martinez, Tesse, Zobairi, and Andriantsitohaina 2005;Barry, Pratico, Savani, and FitzGerald 1998).…”
Section: Complement Activation On Platelet Microparticles (Pmp)mentioning
confidence: 99%